Recognition of Odor Characteristics Based on BP Neural Network - Wu Lei; Fang Jiandong; Zhao Yudong (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper introduces the basic principle and calculation steps of BP neural network algorithm for classification and prediction of odor characteristic parameters. Using the PEN3 electronic nose collects the volatile components of milk and programming BP neural network algorithm under MATLAB condition. This paper validate the use of BP neural network algorithm on milk quality prediction is effective.